1973
DOI: 10.1111/j.1471-0528.1973.tb02154.x
|View full text |Cite
|
Sign up to set email alerts
|

HUMAN PLACENTAL LACTOGEN (HPL) LEVELS IN MATERNAL SERUM DURING ABORTION INDUCED BY INTRA‐ AND EXTRA‐AMNIOTIC INJECTION OF PROSTAGLAND1N F

Abstract: Summary Human placental lactogen (HPL) concentrations in maternal serum were measured by double antibody radioimmunoassay in 25 patients who were undergoing abortion by intra‐ and extra‐amniotic injection of prostaglandin F2α (PGF2α) and by extra‐amniotic injection of hypertonic saline in the first and second trimesters of pregnancy. The injection of 150 ml. of 20 per cent NaCl did not change the HPL level but the extra‐amniotic injection of 5 to 6 mg. of PGF2α and the intra‐amniotic injection of 20 to 25 mg. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1975
1975
1994
1994

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…PGE2 has been found either to depress hPL secretion or to have no effect, whereas PGF2a depresses hPL secretion by placental explants (64). PGF2a adminis tered intra-amniotically causes a rapid reduction in maternal serum hPL levels (167,193). Glucose is essential for hPL secretion by placental ex plants; but when glucose was present in high concentrations in the medium, hPL secretion was apparently inhibited (17).…”
Section: Protein Hormone Production By the Placentamentioning
confidence: 99%
“…PGE2 has been found either to depress hPL secretion or to have no effect, whereas PGF2a depresses hPL secretion by placental explants (64). PGF2a adminis tered intra-amniotically causes a rapid reduction in maternal serum hPL levels (167,193). Glucose is essential for hPL secretion by placental ex plants; but when glucose was present in high concentrations in the medium, hPL secretion was apparently inhibited (17).…”
Section: Protein Hormone Production By the Placentamentioning
confidence: 99%
“…The times of fetal death and abortion are also indicated. Ylikorkala andPennanen (1973) andCorson et al (1975) we found that serum progesterone and HPL levels both decreased half an hour after the intra-amniotic injection of PGFaa, but rose again later. This may indicate that exogenous PG does not immediately and irreversibly alter hormone production by the placenta and the transient rise in levels of progesterone and HPL after half an hour may be due to cell lysis or alterations in placental cell permeability.…”
Section: Resultsmentioning
confidence: 65%
“…The factors responsible for the variation are unknown. Posture has no effect (Ylikorkala et al, 1973), nor does strenuous physical exercise Pavlou et al, 1973) or bedrest , or a period of heavy smoking (Pavlou et al, 1973). There is no change following the infusion of amino acids or ingestion of a protein meal (Tyson et al, 1969;Tatra et al, 1977).…”
Section: (C) Distribution Of Hplmentioning
confidence: 98%